Baccharis magnifica (Asteraceae, Astereae): a striking new species endemic to the summits of Serra do Caparaó, southeastern Brazil - Heiden, Gustavo; Leoni, Lúcio De Souza; Nakajima, Jimi Naoki (Phytotaxa, 2014)
Baccharis magnifica, a new species endemic to the summits of the Serra do Caparaó along the border between Espírito Santo and Minas Gerais, southeastern Brazil, is described. The new species is easily recognized by its shrubby habit, showy green and slightly wine-tinged, long-petiolate leaves with ciliate margins and corymbiform capitulescences. It is morphologically most similar to the allopatric B. macrophylla, which inhabits the mountain summits of the southerly Serra da Mantiqueira range. Illustrations, a distribution map, habitat information, and a conservation assessment are also provided for the new species.